2007
DOI: 10.1128/aac.01453-06
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Spread of mef -Positive Macrolide-Resistant Streptococcus pneumoniae Isolates Causing Invasive Disease in Adults in Germany

Abstract: Isolates (3,845) obtained from German adults with invasive pneumococcal disease between 1992 and 2004 were investigated. Of these, 430 isolates (11.2%) were erythromycin A nonsusceptible. Macrolide resistance genotypes and multilocus sequence types were determined. Among the isolates, 35.6% were erm(B) positive and 63.5% were mef positive. Over the study period, the frequency of resistance rose significantly from 2.2 to 17.0% (P < 0.001). A serotype 14, sequence type 9 clone was the most widespread.Streptococc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
1
7
0
1
Order By: Relevance
“…The MLS B phenotype is prevalent in the majority of European countries, whereas the M phenotype predominates in North America (13,32) and some European countries (England and Germany) (1,33 (38).…”
Section: Discussionmentioning
confidence: 99%
“…The MLS B phenotype is prevalent in the majority of European countries, whereas the M phenotype predominates in North America (13,32) and some European countries (England and Germany) (1,33 (38).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of macrolide resistance mechanisms differs considerably among countries, as shown in Table 2 [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58]. The emergence of pneumococci that carry both ermB and mefE macrolide resistance genes is a cause for concern, especially in Asian countries, Russia, South Africa, and the USA [52,59].…”
Section: Macrolidesmentioning
confidence: 99%
“…Spain 9V -ST156 (serotypes 9V and 14) has been an important cause of IPD in many countries, before and after PCV7 introduction, and usually shows resistance to penicillin and co-trimoxazole [15,78,79]. The prevalence of England 14 -ST9, associated with the spread of macrolide resistance (mefA) in the 1990s in the USA, Canada, the UK, Germany, Norway, Greece, and Italy, decreased significantly after the introduction of PCV7 [44,48,80,81]. The high rate of penicillin and macrolide resistance detected in Asia and the USA was partially related to the spread of Taiwan 19F -ST236 [55,82].…”
Section: Antibiotic Resistance and Serotypes/ Genotypesmentioning
confidence: 99%
“…Despite the interest in this association on the evolution of macrolide and ketolide resistance, very few studies have investigated the population biology of a collection of isolates recovered during different time periods and/or from different geographic origins (13,26). In Spain, population structure studies have shown that resistance in S. pneumoniae international clones, such as clones Spain 9V -3 and England 14 -9, are mainly associated with those endowed with the M phenotype (1, 2), whereas clones Spain 23F -1 and Spain 6B -2 are associated with isolates endowed with the MLS B phenotype (14).…”
mentioning
confidence: 99%